2019
DOI: 10.1177/0022034519865222
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sympathetic Input into Developing Salivary Glands

Abstract: Neuronal signaling is known to be required for salivary gland development, with parasympathetic nerves interacting with the surrounding tissues from early stages to maintain a progenitor cell population and control morphogenesis. In contrast, postganglionic sympathetic nerves arrive late in salivary gland development to perform a secretory function; however, no previous report has shown their role during development. Here, we show that a subset of neuronal cells within the parasympathetic submandibular ganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our transcriptome analyses demonstrated differences in the neuronal progenitor markers associated with the 2 types of salivary gland. Consistent with the recent finding of noradrenergic markers expressed in some Tubb3+ submandibular tissues (Teshima et al 2019), we observed the coexpression of Tubb3 and noradrenergic neuron differentiation marker genes such as Hand2 in the embryonic submandibular gland. However, such noradrenergic marker expression was absent from the early parotid gland.…”
Section: Discussionsupporting
confidence: 92%
“…Our transcriptome analyses demonstrated differences in the neuronal progenitor markers associated with the 2 types of salivary gland. Consistent with the recent finding of noradrenergic markers expressed in some Tubb3+ submandibular tissues (Teshima et al 2019), we observed the coexpression of Tubb3 and noradrenergic neuron differentiation marker genes such as Hand2 in the embryonic submandibular gland. However, such noradrenergic marker expression was absent from the early parotid gland.…”
Section: Discussionsupporting
confidence: 92%
“…The morphology, neurophysiology and neuropharmacology of the mouse CSC-SCG has received considerable investigation over the years (Black et al, 1972;Yokota and Yamauchi, 1974;Banks and Walter, 1975;Inoue, 1975;Lewis and Burton, 1977;Forehand, 1985;Kidd and Heath, 1988;Gibbins, 1991;Kasa et al, 1991;Little and Heath, 1994;Jobling and Gibbins, 1999;El-Fadaly and Kummer, 2003;David et al, 2010;Cadaveira-Mosquera et al, 2012;Pashai et al, 2012;Alberola-Die et al, 2013;Liu and Bean, 2014;Martinez-Pinna et al, 2018;Mitsuoka et al, 2018;Feldman-Goriachnik and Hanani, 2019;Simeone et al, 2019;Rivas-Ramírez et al, 2020). Mouse tissues that receive post-ganglionic projections from the SCG have also been heavily investigated (Krieger et al, 1976;García et al, 1988;Kawaja and Crutcher, 1997;Maklad et al, 2001;Pankevich et al, 2003a,b;Ivanusic et al, 2013;Karlsen et al, 2013;Lindborg et al, 2018;Ziegler et al, 2018;Teshima et al, 2019). Nonetheless, there is no direct evidence that the CSC-SCG complex innervates the carotid bodies of mice, and this is likely on the basis of the presence of sympathetic (i.e., tyrosine-hydroxylase-positive) nerve terminals and adrenergic receptors in these structures (Prieto-Lloret et al, 2007;Roux et al, 2008;Kåhlin et al, 2010;…”
mentioning
confidence: 99%
“…Similar to observations made in the rat cranial parasympathetic ganglia, and different from the observations in the rat and human superior cervical ganglion, these neurons did not co-express DBH (Table 1), indicating that they are unable to synthesize noradrenaline. TH-positive cells can be detected during fetal development, between the 12th and 15th post-conception weeks, at low levels, in the region of the ciliary and submandibular ganglion (Kiyokawa et al 2012;Teshima et al 2019).…”
Section: Neurochemical Features Of the Principal Neurons In The Cranimentioning
confidence: 99%
“…The expression of Hand2, a TF that is expressed in sympathetic neurons and is required for noradrenergic differentiation (Lucas et al 2006;Morikawa et al 2007;Schmidt et al 2009), has also been documented in embryonic cranial parasympathetic neurons. Hand2-positive neurons in the developing SPG (Stanzel et al 2016) and SMG (Teshima et al 2019) are found in regions where DBH or TH can be detected. However, the mutational inactivation of Hand2 in alreadydifferentiated cells does not affect DBH expression, which is transient and disappears during the advanced embryonic stages (Stanzel et al 2016).…”
Section: Embryonic Development Of the Mouse Cranial Parasympathetic Gmentioning
confidence: 99%